Workforce information database system to support production planning in construction projects - Kim, Sang-Chul; Kim, Yong-Woo (Journal of Civil Engineering and Management, 2012)
Information on the capacity of available workforce is important in production planning because a production unit's quantitative and qualitative capacities need to match its assigned loads. In the planning process, assigned loads and quantitative capacity are well defined quantitatively through quantity takeoff and database estimation. However, tracking and managing such workforce information, including skills, accident history and experiences, is a challenging task. This research seeks to develop a prototype workforce information database system that defines not only quantitative data but also qualitative measures in relation to load and capacity. A workforce information database system is described for use in workforce-level production planning. This database system tracks the daily quantitative and qualitative production capacities of each worker. The paper also explored the benefits and its applicability in production planning through a survey.